Tagungsbericht: 10/20 Jahre UNESCO-Konvention zum Erhalt des Immateriellen Kulturerbes – Auftaktveranstaltung zum Doppeljubiläum - Leineweber, Jonas

Politisches Graffiti (Kunst und Politik)

The Omnipotence (al-qudra) and the Will of God (al-irāda) in the Theology of Sayf ad-Dīn al-Āmidī - Husic, Ahmed (The Attributes of God in Islamic Thought: Contemplating Allah)

Arm und ausgegrenzt. Kinderarmut in der Literatur und im lesenden Klassenzimmer. - Kruse, Iris; Terhorst, Sarah („So viel Größenwahn muss sein!”)

"So viel Größenwahn muss sein!". Zur Einführung. - Kruse, Iris; Kanning, Julian (So viel Größenwahn muss sein! Kinderliteratur, Schule und Gesellschaft. Zum Bildungsauftrag des Literaturunterrichts in der Grundschule.)

Towards Comparable Ratings: Quantifying Evaluative Phrases in Physician Reviews - Kersting, Joschka; Geierhos, Michaela (Data Management Technologies and Applications)
We present a concept for quantifying evaluative phrases to later compare rating texts numerically instead of just relying on stars or grades. We achievethis by combining deep learning models in an aspect-based sentiment analysis pipeline along with sentiment weighting, polarity, and correlation analyses that combine deep learning results with metadata. The results provide new insights for the medical field. Our application domain, physician reviews, shows that there are millions of review texts on the Internet that cannot yet be comprehensively analyzed because previous studies have focused on explicit aspects from other domains (e.g., products). We identify, extract, and classify implicit and explicit aspect phrases equally from German-language review texts. To do so, we annotated aspect phrases representing reviews on numerous aspects of a physician, medical practice, or practice staff. We apply the best performing transformer model, XLM-RoBERTa, to a large physician review dataset and correlate the results with existing metadata. As a result, we can show different correlations between the sentiment polarity of certain aspect classes (e.g., friendliness, practice equipment) and physicians’ professions (e.g., surgeon, ophthalmologist). As a result, we have individual numerical scores that contain a variety of information based on deep learning algorithms that extract textual (evaluative) information and metadata from the Web.

Welche Rolle spielt eine reflexive Haltung für eine qualitätsvolle Unterrichtsreflexion? – Zusammenhänge zwischen einer quasi-experimentellen Einstellung und der Reflexionsperformanz von Lehramtsstudierenden [Einzelbeitrag]. - Meier, Jana; Vogelsang, Christoph; Küth, Simon; Scholl , Daniel; Watson, Christina; Seifert, Andreas

Das Unterrichtsplanungsprinzip der Interdependenz – Eine netzwerkanalytische Untersuchung der Begründungsstrukturen beim Planungsentscheiden [Einzelbeitrag]. - Scholl, Daniel; Küth, Simon; Vogelsang, Christoph; Meier, Jana; Watson, Christina; Seifert, Andreas

Eine reflexive Haltung als Grundlage einer hochwertigen Unterrichtsreflexion? Zusammenhänge zwischen einer quasi-experimentellen Einstellung zur Reflexion und der Reflexionsperformanz von Lehramtsstudierenden [Einzelbeitrag]. - Scholl, Daniel; Vogelsang, Christoph; Küth, Simon; Meier, Jana; Watson, Christina; Seifert, Andreas

Der Zyklus von Planung und Reflexion. Zusammenhänge zwischen der generischen Unterrichtsplanungsfähigkeit und der Reflexionskompetenz angehender Lehrkräfte.